TRANSFORMATION OF CHARITIES BY ISLAMIC SOCIAL MOVEMENTS IN YOGYAKARTA, 1912-1931: A HISTORY OF ISLAMIC WEALTH MANAGEMENT - Ghifari Yuristiadhi; Bambang Purwanto (UNISSULA, 2016)
This article was written in order to find a model of the development ofIslamic charities organized by bumiputera in the early 20th century inYogyakarta. This socio-economic history research using historical research methods that utilize primary sources such as archives, photographs, books and newspapers as well as the contemporary of secondary sources such as books, journals, and articles. The conclusion of this article is that the presence of transformation of charities in Yogyakarta in the period 1920s-1930s caused by 1) the dynamic moments around the period of the emergence of privately plantation by European, 2) the implementation of the land reorganization in the region of Yogyakarta Sultanate, 3) the emergence of “urban santri” as the new middle class in urban Yogyakarta, and 4) dynamic Islamic social organizations. In addition, the transformationof charities happens consists of three processes. First, change the concept and definition of waqf be more specific. Secondly, changing of the charities model that presented by the Islamic social movements. Third, shift of waqf and charities authority management that also change management culture. One thing that can be seen from this phenomenon is the emergence of local responses on colonialism with a more elegant and become the new social movements as well as showing the existence of civil society.